Effect of Addition of Turmeric Flour Mix and Papaya Leaf Flour as Feed Additive to the Quality of Broiler Chicken Meat - S E Silaen (Talenta Publisher, 2019)
This study aims to examine the purchase of turmeric flour and papaya flour in the ration on the quality of broiler chicken meat. The design used was a completely randomized design (CRD) with 4 treatments and 5 replications. Treatment with various levels of turmeric flour and papaya leaf flour consists of P0: ration without the addition of turmeric flour and papaya leaf flour; P1: ration with the addition of 0.5% turmeric flour; P2: Ration with addition of 2,5% papaya leaf flour and P3: Ration with addition of 0.5% turmeric flour and 2,5% papaya leaf flour. The parameters studied were the level of meat protein, meat fat content, tenderness of meat and shrinkage of cooked meat. The results showed that the treatment effect was a very significant effect (P<0.01) on meat protein content and meat fat content, meat tenderness showed significantly different results (P<0.05), but did not provide a significant difference (P<0.05) for moisture content of meat and to cook meat shrinkage. The conclusion of this study is the addition of turmeric flour and papaya leaves as feed additives in broiler chickens which have a significant effect on the quality of broiler chicken meat.